Proteomic Analysis Reveals Proteins Involved in the Mode of Action of β-Citronellol Identified From Citrus hystrix DC. Leaf Against Candida albicans - Buakaew, Watunyoo; Pankla Sranujit, Rungnapa; Noysang, Chanai; Krobthong, Sucheewin; Yingchutrakul, Yodying; Thongsri, Yordhathai; Potup, Pachuen; Daowtak, Krai; Usuwanthim, Kanchana (Frontiers in Microbiology, 2022)
Candida albicans is a fungus that lives primarily on the mucosal surfaces of healthy humans, such as the oral cavity, vagina, and gastrointestinal tract. This commensal organism can be controlled by other microbiota, while certain conditions can increase the risk of C. albicans outgrowth and cause disease. Prevalence of the drug-resistant phenotype, as well as the severity of C. albicans infection in immunocompromised patients, presents a challenge for scientists to develop novel, effective treatment, and prevention strategies. β-citronellol is an intriguing active compound of several plants that has been linked to antifungal activity, but data on the mechanism of action in terms of proteomic profiling are lacking. Here, β-citronellol identified from Citrus hystrix DC. leaf against C. albicans were evaluated. A proteomic approach was used to identify potential target proteins involved in the mode of action of β-citronellol. This study identified and discussed three protein groups based on the 126 major proteins that were altered in response to β-citronellol treatment, 46 of which were downregulated and 80 of which were upregulated. Significant protein groups include cell wall proteins (e.g., Als2p, Rbt1p, and Pga4p), cellular stress response enzymes (e.g., Sod1p, Gst2p, and Ddr48p), and ATP synthesis-associated proteins (e.g., Atp3p, Atp7p, Cox1p, and Cobp). Results demonstrated the complexities of protein interactions influenced by β-citronellol treatment and highlighted the potential of antifungal activity for future clinical and drug development research.